Perancangan Video Musik “Mayfly” sebagai Media Promosi Idol Group Oriana - Immanuel Aria Kristono; Martin Setyawan; Peni Pratiwi (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Idol or Aidoru (アイドル) is a term or another word for Idol in Japan which can be interpreted as a famous artist who can take part in various fields. Idol Oriana is a local idol from Solo who made their debut on August 28, 2023. But until now Oriana Idol only has an original song called Mayfly and Oriana Idol wants to well known. Oriana also make a music video for the song “Mayfly” to promote Oriana Idol more widely. Therefore, this research was made to create a music video as a promotional media for Oriana Idol. The result of this research is a music video as a promotional media. The music video focuses on the choreographed performance of the song “Mayfly” and the visuals of the members, with a short storyline. This reseacrh can be a solution for Oriana to promote Idol Oriana further.